2017
DOI: 10.1071/fp17128
|View full text |Cite
|
Sign up to set email alerts
|

No escape? Costs and benefits of leaf de-submergence in the pasture grass Chloris gayana under different flooding regimes

Abstract: Elongation-induced leaf emergence is one way for plants to deal with complete submergence by ‘escaping’ from water. This growth strategy is hypothesised to be more beneficial under single long-term submergence than under repeated short-term submergence events (i.e. fluctuating environment), as costs of repeated plant ‘adjustment’ would exceed the initial benefits of shoot elongation. To test this idea, 2-week-old plants of Chloris gayana Kunth. cv. Fine Cut (a submergence-tolerant cultivar first selected by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…The regulation of hydraulic conductivity in roots seems to be exerted by a protein kinase that links O 2 and potassium sensing in soils, thus modulating tolerance to hypoxia ( Shahzad et al , 2016 ). The potential reduction in hydraulic conductivity during post-submergence remains to be demonstrated in different plants but it certainly would lead to dehydration and leaf wilting in shoots ( Striker et al , 2017 ; Yeung et al , 2018 ), symptoms that are likely to be due to the inability to efficiently close the stomata ( Postiglione and Muday, 2020 ). Although stomata closure can prevent water loss by transpiration, it also limits carbon dioxide uptake and thus photosynthesis, so this process should be tightly regulated during the post-hypoxia recovery ( Fig.…”
Section: Dehydration Chlorophyll Catabolism and Senescence Are Paramount Processes During Post-hypoxia Recoverymentioning
confidence: 99%
“…The regulation of hydraulic conductivity in roots seems to be exerted by a protein kinase that links O 2 and potassium sensing in soils, thus modulating tolerance to hypoxia ( Shahzad et al , 2016 ). The potential reduction in hydraulic conductivity during post-submergence remains to be demonstrated in different plants but it certainly would lead to dehydration and leaf wilting in shoots ( Striker et al , 2017 ; Yeung et al , 2018 ), symptoms that are likely to be due to the inability to efficiently close the stomata ( Postiglione and Muday, 2020 ). Although stomata closure can prevent water loss by transpiration, it also limits carbon dioxide uptake and thus photosynthesis, so this process should be tightly regulated during the post-hypoxia recovery ( Fig.…”
Section: Dehydration Chlorophyll Catabolism and Senescence Are Paramount Processes During Post-hypoxia Recoverymentioning
confidence: 99%
“…It is alleged that shoot growth and increased shoot to root ratio (S:R) during submergence can induce a better balance between gas transport capacity (oxygen source) and root oxygen consumption (oxygen sink) when plants are able to succeed in the process of emerging leaves above water ("escape strategy"; [34,35]). However, an increased S:R can also constrain plant recovery after de-submergence if water loss by transpiration cannot be replenished by root water uptake, regardless of whether leaf emergence was achieved, as seen in the forage grass Chloris gayana subjected to 1 week of full submergence [24]. In our experiment, S:R ratio upon de-submergence was negatively related to the RGR during the recovery phase across L. japonicus genotypes.…”
Section: Discussionmentioning
confidence: 58%
“…The elongation induction strategy of leaf blade of Chloris gayana Kunth. under different water flooding time and mode, and found that long-term water flooding is more beneficial to plant growth than repeated water flooding was studied in detail Striker et al, 2017). The changes of biomass, photosynthesis and other physiological and biochemical characteristics of Alternanthera philoxeroides (Mart.)…”
Section: вісник сумського національного аграрного університетуmentioning
confidence: 99%